Viscoelastic properties of poly(ε‐caprolactone)/clay nanocomposites in solid and in melt state. Issue 3 (11th September 2015) - Nikolic, Marija S.; Mitric, Miodrag; Dapcevic, Aleksandra; Djonlagic, Jasna
ABSTRACT Viscoelastic properties in solid and in melt state of poly(ε‐caprolactone), PCL, nanocomposites with organomodified clays (Cloisite30B and Cloisite15A) are thoroughly investigated. Although WAXD is insensitive to the difference in the nanocomposites structure, the melt rheology reveals pronounced differences between the two series. Melt yield stress values, obtained from fittings by the Carreau–Yasuda model, are used as a measure of partial exfoliation of the clay. Temperature dependence of the shift factors, used for time–temperature superposition of the modulus curves, yields similar values of the flow activation energies for all the samples. Temperature dependences of the dynamic modulus and loss factor of solid nanocomposites were correlated to the structural differences deduced from the melt rheology. The increase in the storage modulus is compared to the theoretical predictions from the Halpin–Tsai model. The effective aspect ratio obtained from this comparison agrees reasonably with the value estimated from the melt rheology. © 2015 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2016, 133, 42896.